ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL GEOMETRI POKOK BAHASAN BANGUN RUANG SISI DATAR - Siti Juanti; Rina Karolina; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe the difficulties of students and the factors causing students to have difficulty in solving the problem of getting up the flat side space. This type of research is descriptive. The subject of this research is SMPN 1 Naringgul. The population of this study was all students of class IX at SMPN 1 Naringgul, the study sample was taken using a random sample technique of 5 people. Data collection techniques in this study were tests, interviews, and documentation. Data validity uses method triangulation, while data analysis techniques use reduction, data presentation, and verification. The results of the study concluded that 1) students experience errors in receiving information, students have difficulty in stating what needs to be known and what is asked. Difficulties in receiving information were obtained (45%). 2) errors related to the concept of building flat side space, students' difficulties in using formulas and applying them, errors in finding the surface area of beams, errors in modeling problem solving, errors in calculating. Difficulties related to the concept were obtained (64%).